Monitoring Binding of HIV‐1 Capsid Assembly Inhibitors Using 19F Ligand‐and 15N Protein‐Based NMR and X‐ray Crystallography: Early Hit Validation of a Benzodiazepine Series. Issue 3 (10th February 2013) - Goudreau, Nathalie; Coulombe, René; Faucher, Anne‐Marie; Grand‐Maître, Chantal; Lacoste, Jean‐Eric; Lemke, Christopher T.; Malenfant, Eric; Bousquet, Yves; Fader, Lee; Simoneau, Bruno; Mercier, Jean‐François; Titolo, Steve; et al.
Abstract The emergence of resistance to existing classes of antiretroviral drugs underlines the need to find novel human immunodeficiency virus (HIV)‐1 targets for drug discovery. The viral capsid protein (CA) represents one such potential target. Recently, a series of benzodiazepine inhibitors was identified via high‐throughput screening using an in vitro capsid assembly assay (CAA). Here, we demonstrate how a combination of NMR and X‐ray co‐crystallography allowed for the rapid characterization of the early hits from this inhibitor series. Ligand‐based 19F NMR was used to confirm inhibitor binding specificity and reversibility as well as to identify the N‐terminal domain of the capsid (CANTD) as its molecular target. Protein‐based NMR (1H and 15N chemical shift perturbation analysis) identified key residues within the CANTD involved in inhibitor binding, while X‐ray co‐crystallography confirmed the inhibitor binding site and its binding mode. Based on these results, two conformationally restricted cyclic inhibitors were designed to further validate the possible binding modes. These studies were crucial to early hit confirmation and subsequent lead optimization.